Pengalaman Kedukaan pada Individu Remaja yang Kehilangan Orang Tua Akibat Kematian - Fadia Nafa Rahmadiani; Siti Jaro'ah; Fitrania Maghfiroh (Buletin Riset Psikologi dan Kesehatan Mental, 2026)
The death of a parent during adolescence can affect emotional, cognitive, and behavioral aspects, making it important to understand this experience in depth. This study explores the grief experiences of adolescents who have lost a parent, focusing on their thoughts, feelings, and behaviors related to the loss. A qualitative phenomenological approach was used through online semi-structured interviews with three participants aged 18–20 years, analyzed using Interpretative Phenomenological Analysis (IPA). The findings identified seven themes: pre-loss experiences, loss event, post-loss emotional reactions, post-loss support, coping and adaptation, meaning-making of loss, and impact of loss. Scientifically, the study indicates that anticipatory grief does not necessarily foster mental preparedness, while strained past relationships may lead to reduced interest in activities after loss. Practically, these findings may guide school counselors and psychologists in designing adolescent grief support programs focused on processing distressing memories, strengthening family support, and fostering spiritual resilience.